Consistency analysis of microRNA‐arm expression reveals microRNA‐369‐5p/3p as tumor suppressors in gastric cancer. Issue 7 (17th June 2019) - Dong, Lei; Zhang, Zhengyi; Xu, Jiayue; Wang, Fang; Ma, Yanni; Li, Feng; Shen, Chao; Liu, Ziwen; Zhang, Junwu; Liu, Changzheng; Yi, Ping; Yu, Jia
Abstract : The 5p and 3p arms of microRNA (miRNA) are typically generated from the same precursor, and one arm influences protein output, while the other has a short half‐life. However, a few miR‐5p/3p pairs have been reported to co‐exist in cancer cells. Here, we performed a genome‐wide analysis of miRNA expression in gastric cancer (GC) cells to systematically investigate the co‐expression profile of miR‐5p/3p in gastric tumorigenesis. We discovered that only 41 miR‐5p/3p pairs out of 1749 analyzed miRNA were co‐expressed. Specifically, abnormal expression of miR‐369‐5p and miR‐369‐3p was correlated with GC progression. Importantly, both in vitro and in vivo assays revealed that miR‐369‐5p and miR‐369‐3p exhibited tumor‐suppressive roles by regulating jun proto‐oncogene and v‐akt murine thymoma viral oncogene homolog 1 function in GC cells, respectively. Moreover, we observed that miR‐369 was inactivated in GC tissues due to DNA methylation. We also showed that inhibition of miR‐369‐5p/3p attenuated the effect of azacitidine (AZA) treatment on suppressing cell growth and invasion. These results suggest that the therapeutic efficacy of AZA in GC is at least partly attributable to miR‐369 activation. Overall, our findings provide convincing evidence that both the 5p and 3p arms of miRNA co‐expressed in GC and DNA methylation‐induced miR‐369 signaling contribute to GC progression. Abstract : The microRNA‐369 (miR‐369) gene may undergo nonprevalent processing to produce two relatively stable arms in gastric cancer cells. Abnormal DNA methylation blunts miR‐369 expression and results in a decrease in two tumor suppressors (miR‐369‐5p and ‐3p). Hypomethylating agents can contribute to miR‐369 activation, suggesting this as a potential therapeutic target of epigenetic drugs.